2017
DOI: 10.1038/ng.3979
|View full text |Cite
|
Sign up to set email alerts
|

Predicting causal variants affecting expression by using whole-genome sequencing and RNA-seq from multiple human tissues

Abstract: Genetic association mapping produces statistical links between phenotypes and genomic regions, but identifying causal variants remains difficult. Whole-genome sequencing (WGS) can help by providing complete knowledge of all genetic variants, but it is financially prohibitive for well-powered GWAS studies. We performed mapping of expression quantitative trait loci (eQTLs) with WGS and RNA-seq, and found that lead eQTL variants called with WGS were more likely to be causal. Through simulations, we derived proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 57 publications
4
81
0
Order By: Relevance
“…However, even within a cell or tissue type, such data are often mutually discordant: one study examining six epigenomic datasets in K562 cells found that 49% of functional regulators did not overlap any of the six annotation sets, and another 40% only overlapped one of the six (11). Similarly, the Roadmap Epigenomics Consortium (12) inferred cell type-specific regulatory elements using chromatin marks, but only a minority of GWAS SNPs overlap these elements (except in blood) (13). Therefore, epigenomic data alone are inadequate for predicting functional regulatory variants in a given cell type.…”
Section: Challenges In Predicting a Variant's Functional Consequencesmentioning
confidence: 99%
“…However, even within a cell or tissue type, such data are often mutually discordant: one study examining six epigenomic datasets in K562 cells found that 49% of functional regulators did not overlap any of the six annotation sets, and another 40% only overlapped one of the six (11). Similarly, the Roadmap Epigenomics Consortium (12) inferred cell type-specific regulatory elements using chromatin marks, but only a minority of GWAS SNPs overlap these elements (except in blood) (13). Therefore, epigenomic data alone are inadequate for predicting functional regulatory variants in a given cell type.…”
Section: Challenges In Predicting a Variant's Functional Consequencesmentioning
confidence: 99%
“…To discover multiple independent eQTLs, we applied a stepwise regression procedure as described in Brown et al 75 . Briefly, we started from the set of eGenes discovered in the first pass of association analysis (FDR < 1%).…”
Section: Rnaseq Quality Assessment and Data Normalizationmentioning
confidence: 99%
“…An association with species-specific OCRs and expression changes would support that the state changes are biologically relevant. To measure association with expression changes, we compared to known human adipose expression quantitative trait loci (eQTL) (18).…”
Section: Species-specific Ocr States Correlate With Cis-regulatory DImentioning
confidence: 99%